MENINGKATKAN SISTEM PERLINDUNGAN ANAK BAIK PENCEGAHAN MAUPUN PENANGANAN DENGAN MEMPERTIMBANGKAN TANTANGAN DAN ANCAMAN YANG DIHADAPI ANAK - Kirana, Yanti (STIH Awang Long Samarinda, 2018)
General Dictionary of Indonesian protection means a place of refuge or an act (thing) to protect, for example giving protection to weak people. Legal protection is an action that is protected by legal subjects with applicable regulations and their implementation can be imposed by a regulation. Law Number 23 of 2002 concerning the Protection of Children Has Been Changed by Law Number 35 of 2014 concerning Amendments to Law Number 23 of 2002 concerning Protection of Children entitled to protection from Rescue in political activities, involvement in dispute release, involvement in social unrest, involvement in events involving non-violence, involvement in war and sexual crimes.